Self-Templating of Metal-Driven Supramolecular Self-Assembly: A General Approach toward 1D Inorganic Nanotubes - Qiao, Yan; Wang, Yijie; Yang, Zhiyi; Lin, Yiyang; Huang, Jianbin (Chemistry of materials, 2011)
The rational design of one-dimensional (1D) inorganic nanomaterials directed by self-assembled soft matters is one of the most attractive subjects in modern chemistry. In this work, the self-templating approach based on metal−cholate supramolecular self-assemblies is reported, which is distinct from the traditional soft template method. Under the framework of self-templating, metal ions can serve as both the inorganic precursor and constituent of the template; additional precursors which may change the solution conditions and interfere with the soft templates are not needed. It is demonstrated that self-templating method is a general approach to synthesize a series of 1D inorganic nanotubes including ZnS, CuS, NiS, CdS, CoS, ZnSe, and ZnTe nanotubes. Moreover, the structural diversity and dynamic nature of organic architectures allow the preparation of size and shape-adjustable 1D nanotubes through conveniently temporal and thermal controls. A possible mechanism for nanotube formation is also proposed.